The Role of the Entrepreneurship Character of Islamic Students in the Economic Independence of Islamic Boarding Schools in Bangkalan: Peran Karakter Entrepreneurship Santri dalam Kemandirian Ekonomi Pesantren di Bangkalan - Taufiqur Rahman; Alan Su’ud Ma’adi (El-Qist: Journal of Islamic Economics and Business (JIEB), 2022)
Abstract: This study aims to find out the entrepreneurial character of students in Islamic boarding schools, which functions to see phenomenologically the involvement of students in realizing the economic independence of Islamic boarding schools because, so far, Islamic boarding schools are only seen as Islamic educational institutions, but Islamic boarding schools as a community empowerment institution in the economic field still have not been exposed in detail and holistically. This study focuses on knowing the entrepreneurial character of students at Islamic boarding schools in the Bangkalan district and knowing the role of the entrepreneurial character of students with their involvement in advancing the economic independence of Islamic boarding schools in Bangkalan Regency, especially in Al-Hikam and Raudlatul Mutaallimin Islamic Boarding School. This study uses a qualitative approach. The data collection technique uses documentation involving observation and in-depth interviews with several Islamic boarding schools students and caregivers (Kiai) and boarding school administrators. At the same time, data analysis uses descriptive phenomenological analysis to elucidate descriptively and introspectively all consciousness of the human form and its experience in sensory, conceptual, moral, aesthetic, and religious aspects. The results of this study show that the model for inculcating entrepreneurial character values in two Islamic boarding schools in Bangkalan Regency is through explanations to students about the success of the Prophet Muhammad as an entrepreneur and through motivational words from caregivers during recitation activities of Yellow Book related to the importance of the entrepreneurship. At the same time, the role of the character of entrepreneurship in the economic independence of Islamic boarding schools is framed as being an assistant caregiver as a facilitator for other students for training students and proposing ideas to caregivers in the selection of business units established in the Islamic boarding school. Keywords: Character; Entrepreneurship; Independence; Islamic Boarding School.   Abstrak: Penelitian ini bertujuan untuk mengetahui karakter wirausaha santri di pesantren, yang berfungsi untuk melihat secara fenomenologis keterlibatan santri dalam mewujudkan kemandirian ekonomi pesantren karena selama ini pesantren hanya dipandang sebagai lembaga pendidikan semata. Sehingga pesantren sebagai lembaga pemberdayaan masyarakat di bidang ekonomi masih belum terekspos secara detail dan holistik. Penelitian ini berfokus untuk mengetahui karakter wirausaha santri pondok pesantren di Kabupaten bangkalan dan ingin mengetahui peran karakter wirausaha santri dengan keterlibatannya dalam memajukan kemandirian ekonomi pesantren khususnya di pesantren al-Hikam dan Raudlatul Mutaallimin yang menjadi objek. Penelitian ini menggunakan pendekatan kualitatif. Teknik pengumpulan data menggunakan dokumentasi berupa observasi dan wawancara mendalam dengan beberapa santri, pengurus dan Kiai pesantren. Sementara itu, analisis data menggunakan analisis deskriptif fenomenologis untuk menguraikan secara deskriptif dan introspektif seluruh kesadaran bentuk manusia dan pengalamannya dalam aspek indrawi, konseptual, moral, estetika, dan religi. Hasil penelitian ini menunjukkan bahwa model penanaman nilai karakter kewirausahaan di dua pesantren di Kabupaten Bangkalan tersebut adalah melalui penjelasan kepada santri tentang keberhasilan Nabi Muhammad Saw. sebagai wirausahawan, dan juga melalui kata-kata motivasi dari Kiai saat kegiatan pengajian kitab Kuning. Sementara itu, peran karakter entrepreneurship dalam kemandirian ekonomi pesantren dibingkai sebagai asisten Kiai sebagai fasilitator bagi santri lainnya untuk melatih santri dan memberikan ide kepada pengasuh dalam pemilihan unit usaha yang didirikan di pesantren. Kata Kunci: Karakter; Kewiraswastaan; Kemandirian; Pondok Pesantren.